A biópsia de linfonodo sentinela não deve ser recomendada para pacientes portadores de melanoma espesso - de Oliveira Filho, Renato Santos [UNESP]; da Silva, Allisson Monteiro; de Oliveira, Daniel Arcuschin; Oliveira, Gustavo Gianotto; Nahas, Fabio Xerfan (FapUNIFESP (SciELO), 2013)
Objective: To ascertain whether there is any relationship between the state of the sentinel lymph node histopathology, recurrence and mortality from thick melanoma in patients undergoing SLNB over a long follow-up. Methods: Eighty-six patients with thick melanoma undergoing SLNB were selected from a prospective database. Lymphoscintigraphy, lymphatic mapping and intraoperative gamma probe detection were performed in all patients. The sentinel lymph node (SLN) was analyzed by HE and immunohistochemistry. Complete lymphadenectomy was indicated for patients with positive sentinel node. The histopathological SLN status was related to the rate of recurrence and mortality from melanoma. Results: One hundred and sixty-six SLNs were taken from the 86 patients. Ages ranged from 18 to 73 years. There were 47 women and 39 men. Micrometastases were found in 44 patients. Forty-two patients underwent complete lymphadenectomy. Seven other patients had positive lymph node. Among the 44 patients with positive sentinel node, there were 20 recurrences and 15 deaths. There were 18 recurrences and 12 deaths in the group with negative SLN. The Breslow thickness was not correlated with the histopathological SLN status. The histopathological SLN status did not affect the rates of recurrence and mortality (Fisher test, p = 1.00). The median follow-up was 69 months. Conclusion: Considering the lack of evidence of benefit, SLNB should not be indicated for patients with thick melanoma outside of clinical studies.
Sentinel node biopsy should not be recommended for patients with thick melanoma
Keywords: Melanoma; Mortality; Neoplasms micrometastasis; Recurrence; Sentinel lymph node biopsy